Rethinking the airport experience with indoor location-based services - Kachiungo, Emerson Lukamba Kalitangue (2019)
The Customer Experience (CX) has emerged as a key instrument for customer relationship management for companies across all sectors of the economy. The airport Customer Experience, in particular, is often shadowed by stress and anxiety. These emotions are primarily connected with the complexity of the terminals and some processes like security screening and customs. Indoor location-based service is an emerging technology that uses the abilities of mobile devices, location technologies, and mobile networks to provide personalized and instant information or service based on the user location. The purpose of this study is to understand how Indoor location-based services can contribute positively to their airport experience. To do so, the main characteristics of the airport experience and the capabilities of the technology are explored. Secondary data was collected from various literature, articles, and reports. Additionally, a survey was conducted to gain insights on the passenger's reaction to technology. The results are incredibly positive and show that passenger value the applications that ILBS can bring to the airport experience.